Influence of meadowsweet ordinary (Filipendula vulgaris) extract on behavior in models of anxiety - A. V. Kaygorodtsev (Бюллетень сибирской медицины)
Influence of water and water-ethanol extracts of meadowsweet ordinary on behavior of albino mice in anxiety models is studied. Anxiolytic action of extracts estimated on animals behavior in an elevated plus-maze, an «open field» and in the test of emotional reaction. It was defined that water and 95% water-ethanol extracts of meadowsweet ordinary render the most expressed anxiolytic action and surpass in activity an valerian extract.